2017
DOI: 10.3390/ma10101133
|View full text |Cite
|
Sign up to set email alerts
|

A New Ion-Imprinted Chitosan-Based Membrane with an Azo-Derivative Ligand for the Efficient Removal of Pd(II)

Abstract: Herein, we described the synthesis of a novel ion-imprinted membrane for the detection of palladium(II) prepared through the glutaraldehyde crosslinking of chitosan with a 4-[(4-Hydroxy)phenylazo]benzenesulfonic acid ligand trapped into the membrane. The imprinting technology was used to improve adsorption capacity and adsorption selectivity, and was combined with some advantages of the developed membrane, such as low cost and ease of preparation, water-friendly synthesis, and high biocompatible chitosan mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 48 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Materials generated by this technique present high chemical resistance, thermal stability, good mechanical properties and reusability [23]. Hence, considering the advantages of MI, many scientists have been using this technique to develop various advanced materials [24][25][26], such as membranes [27,28], beads [29], particles [30,31], micro-and nano-gels [32,33] or thin films [34,35], to be utilized as separation tools [36], catalysts [37] or sensors and biosensors [38] for metal recovery [39,40], drug delivery [41] and ternary mixture separation [42]. In this context, some authors have already reported the use of MI for developing TNT-MIPs using surface imprinting of silica nanoparticles [43] and nanotubes [44] or bulk imprinting of films [16,27].…”
Section: Introductionmentioning
confidence: 99%
“…Materials generated by this technique present high chemical resistance, thermal stability, good mechanical properties and reusability [23]. Hence, considering the advantages of MI, many scientists have been using this technique to develop various advanced materials [24][25][26], such as membranes [27,28], beads [29], particles [30,31], micro-and nano-gels [32,33] or thin films [34,35], to be utilized as separation tools [36], catalysts [37] or sensors and biosensors [38] for metal recovery [39,40], drug delivery [41] and ternary mixture separation [42]. In this context, some authors have already reported the use of MI for developing TNT-MIPs using surface imprinting of silica nanoparticles [43] and nanotubes [44] or bulk imprinting of films [16,27].…”
Section: Introductionmentioning
confidence: 99%
“…In many studies CS was used as imprinting functional polymer that, via crosslinking reactions in presence of the template, creates the imprinting effect and enhances insolubility and mechanical strength. Various crosslinker agents have been used such as glutaraldehyde [ 43 , 44 ] epichlorohydrin [ 45 , 46 ], sulfuric acid, glyoxal [ 47 ], and so on.…”
Section: Different Biomass Waste In Mip Technologymentioning
confidence: 99%
“…In particular, CTS is an abundant polysaccharide whose amino and hydroxyl groups can chelate with heavy metal ions. CTS can be modified to improve the stability of CTS-based adsorption materials, which has permitted the development and use of various modified CTS membranes for treating industrial wastewater containing heavy metal ions (Bello et al., 2017;Hu, Deng, Hu, Duan, & Zhai, 2016). For example, Reiad, Salam, Abadir, and Harraz (2012) prepared a microporous CTS membrane using PEG-6000 as a porogen to adsorb Fe 2+ and Mn 2+ in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%